ANALISIS PENERAPAN AKUNTANSI KEUANGAN PADA DESA PONDOK SIGUANG KECAMATAN DANAU KERINCI BARAT KABUPATEN KERINCI - Zesmi Kusmila; Cyntia Carolina (Jurnal Bina Bangsa Ekonomika, 2024)
A village is a legal community unit that has territorial boundaries and is authorized to regulate and manage government affairs and the interests of local communities based on community initiatives in the government system of the unitary state of the Republic of Indonesia. This research aims to determine the application of financial accounting in Pondok Siguang Village, West Lake Kerinci District, Kerinci Regency, researchers used Primary and Secondary Data in the form of written documents and direct interviews. This research uses the accounting cycle guidelines of the IAI-KASP Village Financial Accounting Assistance Guidelines, 2015 and Generally Accepted Accounting Principles